Development of Physics Students Worksheets with Scientific Approaches to Improve Skills Critical Thinking and High School Student Learning Outcomes - Algiranto Algiranto; Sulistiyono Sulistiyono (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2020)
Low critical thinking skills and student learning outcomes in physics, especially in class X students of Muhammadiyah Imogiri High School becomes the background of this research. This research aims to (1) produce student worksheet products with a scientific approach that is appropriate to be used to improve critical thinking skills and high school student learning outcomes, (2) find out the improvement of students' critical thinking skills after using student worksheet with a scientific approach in the physics learning process. (3) knowing the increase in student learning outcomes after using student worksheets with a scientific approach to the development results. This research is a research and development (R&D) development with a 4-D model that is defined, design, develop, and disseminate. The subjects of the study were students of class X IPA of Muhammadiyah Imogiri High School. The results showed: (1) obtained student worksheet with a scientific approach that is suitable for use in learning in class X high school on temperature and heat material, based on the results of the assessment of the material validator included in the category (very good), from the media validator included in the category (good) and language validator is included in the category (Very Good) so that the Development Worksheet is feasible to be used for learning activities, (2) Students' critical thinking skills have increased in terms of the gain value of the pretest-posttest results in the moderate category with a gain value of 0.67. (3) the improvement of cognitive aspects of learning outcomes is indicated by the standard value of gain <g> of 0.73 (high). From these results, it can be concluded that the development worksheet can improve critical thinking skills and student learning outcomes.